A STUDY OF MAGNITUDE OF IRON DEFICIENCY IN QATARY ADULTS DIAGNOSED TO HAVE IRON DEFICIENCY ANEMIA - Khan, A. Sattar (Journal of Ayub Medical College Abbottabad, 2000)
Background: Dietary requirement for iron is negligible and iron deficiency is very unlikely unless there is inadequate intake, utilization, absorption or excessive loss of blood. Iron status however differs from population to population depending upon a number of factors. Iron deficiency anemia occurs at a stage when iron stores are absolutely finished. This study was done to look for magnitude of iron deficiency through various parameters of iron deficiency' in the subjects diagnosed to have iron deficiency anemia in Qatary adults. Methods: Among patients visiting outpatient departments of Hamad Medical Corporation, Qatar in the year 1993-1994, 108 were diagnosed for iron-deficiency anemia. Serum Iron, TIBC and transferrin saturation were done to look for exact status of iron deficiency'. Results: Out of 108, 24% were males and 76% females. In these patient's serum iron (21.73 pg/dl) and transferrin saturation (6.96%) was low while the total iron binding capacity' (TIBC) was within normal range. In male's iron (20.73 pg/dl) and transferrin saturation (5.68%) was comparatively lower than females having iron 24.41 (µg/dl and transferrin saturation 7.36 % respectively